A comprehensive review on applications of Raspberry Pi - Mathe, Sudha Ellison; Kondaveeti, Hari Kishan; Vappangi, Suseela; Vanambathina, Sunny Dayal; Kumaravelu, Nandeesh Kumar (Computer science review, 2024)
Raspberry Pi is an invaluable and popular prototyping tool in scientific research for experimenting with a wide variety of ideas, ranging from simple to complex projects. This review article explores how Raspberry Pi is used in various studies, discussing its pros and cons along with its applications in various domains such as home automation, agriculture, healthcare, industrial control, and advanced research. Our aim is to provide a useful resource for researchers, educators, students, product developers, and enthusiasts, helping them to grasp the current status and discover new research possibilities using Raspberry Pi. •This article provides a comprehensive overview of the various applications of Raspberry Pi in different domains.•This article discusses the benefits of using Raspberry Pi for prototyping and automation and its limitations.•This article also discusses the challenges, and related issues associated with prototyping with Raspberry Pi.•This article serves as a valuable reference for those looking to understand the current state of the art in a specific field for developing a solution.